Iron-based amorphous alloy, preparation method thereof and application of iron-based amorphous alloy in degradation of tetracycline antibiotics
By adsorbing and degrading tetracycline antibiotics using iron-based amorphous alloys, the problem of ineffective degrading tetracycline antibiotics in the prior art has been solved, and an efficient removal rate and easy recovery effect has been achieved.
Patent Information
- Application Number
- CN202411452800.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing technology cannot effectively degrade tetracycline antibiotic pollution, and the adsorption method can only achieve the transfer of pollutants without degradation. The biodegradation efficiency is low and limited by the induction of microorganisms and the richness of carbon and nitrogen sources. The metal organic framework materials are costly and Difficult to apply on a large scale.
Iron-based amorphous alloy with a molecular formula of FexSiyBz, and iron-based amorphous alloy strips are prepared by melting and single-roll rolling method, and applied to wastewater containing tetracycline antibiotics, and degrading tetracycline through adsorption and chemical reactions. Antibiotic-like.
Iron-based amorphous alloys have high amorphous formation ability and tolerant preparation process conditions. They can adsorb and degrade tetracycline antibiotics under low activation energy, significantly improve the removal rate, and are easier to recover after the degradation reaction.
Smart Images

Figure CN119506738A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of amorphous alloy materials and antibiotic degradation, and in particular to an iron-based amorphous alloy and a preparation method thereof and application in degrading tetracycline antibiotics. Background Art
[0002] Antibiotics are one of the most important drugs for preventing and treating bacterial infections in humans. They are also widely used in animal husbandry and aquaculture as drugs for preventing and treating infectious diseases in animals and as antibacterial growth-promoting additives. These antibiotics may enter environmental water and soil through farmland runoff, veterinary wastewater and excrement, causing environmental pollution problems.
[0003] In recent years, there are roughly three types of antibiotic wastewater treatment technologies that have been most widely studied, namely adsorption, biodegradation and advanced oxidation technology.
[0004] Adsorption is a common separation and treatment technology for pollutants in water. It is simple to operate, economical and efficient, and has no side effects. The core of adsorption technology is the development of adsorbents. Generally, porous materials with low cost, rich functional groups, and large specific surface area are selected. Common adsorbents in existing research include activated carbon, biochar, bentonite, chitosan, and graphene. Tetracycline is the most common antibiotic in adsorption research because it has polar functional groups such as carboxyl and acylamino groups, and has strong adsorption properties, making it very suitable for removal by adsorption. However, this technology can only realize the transfer of antibiotic pollutants between different phases, and cannot achieve the degradation of antibiotics. At the same time, the corrosion resistance of the adsorbent, the recycling and use problems, and the treatment of waste adsorbents have all limited the practical application of the adsorption method.
[0005] Biodegradation is the main way antibiotics are degraded under natural conditions, and it is also a common technology used by sewage treatment plants to treat organic wastewater. The research hotspots of biodegradation are removal mechanisms and operating conditions. However, for a variety of reasons, not all antibiotics can be effectively degraded. First, microorganisms prefer organic matter with rich carbon and nitrogen sources in wastewater rather than antibiotics with lower concentrations. Secondly, the specific degradation enzymes required for degradation cannot be induced at low concentrations of antibiotics. In addition, the biological toxicity of antibiotics also greatly inhibits the treatment performance of biodegradation.
[0006] Metal-organic frameworks (MOFs) are considered to be a feasible material for the photocatalytic degradation of antibiotics. However, due to their harsh manufacturing conditions and high costs, they cannot be applied to large-scale sewage treatment and other problems, making them difficult to use on a large scale.
[0007] In recent years, zero-valent iron has attracted more and more attention due to its wide applicability, low price, simple operation and non-toxicity in treating organic matter. There have also been studies on the use of zero-valent nano-iron to adsorb and degrade tetracycline. Its degradation products are mainly deaminated tetracycline analogs. The zero-valent iron in water is converted into ferric hydroxide, which then adsorbs tetracycline and forms degradation products within 15 to 240 minutes. Tetracycline is an efficient chelating agent for high-valent metal ions. Tetracycline can chelate with iron ions in water to form Fe-TC complexes. This complex cannot reduce the antibiotic activity of tetracycline, so it should be removed from polluted wastewater before it enters the sewage treatment plant. At the same time, for zero-valent iron powder of crystalline metal element, problems such as agglomeration and oxidation are prone to occur during storage, transportation and application, which leads to a significant decrease in its degradation efficiency. Summary of the invention
[0008] In order to solve the problems existing in the above-mentioned prior art, the present disclosure aims to provide an iron-based amorphous alloy and a preparation method thereof and an application in degrading tetracycline antibiotics, so as to solve the problem that the prior art cannot effectively degrade tetracycline antibiotic pollution.
[0009] The present invention discloses an iron-based amorphous alloy, the molecular formula of which is FexSiyBz, wherein x, y, and z represent the atomic percentages of Fe, Si, and B in the alloy, respectively, 74≤x≤84, 6≤y≤16, 6≤z≤16, and x+y+z=100.
[0010] The present disclosure also provides a method for preparing the iron-based amorphous alloy as described above, comprising the following steps:
[0011] S1, melting the raw materials in a melting furnace in an inert atmosphere according to proportion to prepare an iron-based amorphous alloy;
[0012] S2. The iron-based amorphous alloy obtained in step S1 is prepared into an iron-based amorphous alloy strip by a single-roller strip spinning method.
[0013] Preferably, the thickness of the iron-based amorphous alloy strip is 10 μm to 200 μm.
[0014] Preferably, the preparation method further comprises:
[0015] S3, cutting the iron-based amorphous alloy strip into sheet strips with a length of 10 mm.
[0016] The present disclosure also provides an application of an iron-based amorphous alloy, wherein the iron-based amorphous alloy is applied to the treatment of wastewater containing tetracycline antibiotics to degrade tetracycline antibiotics.
[0017] Preferably, in the wastewater containing tetracycline antibiotics, the concentration of the tetracycline antibiotics is 10-200 mg / L.
[0018] Preferably, the pH value of the wastewater containing tetracycline antibiotics is 3.3-9.
[0019] Preferably, the pH value of the wastewater containing tetracycline antibiotics is 4-9.
[0020] Preferably, the added amount of the iron-based amorphous alloy strip is greater than or equal to 10 g / L.
[0021] Preferably, the temperature of the wastewater containing tetracycline antibiotics is 30-40°C.
[0022] The advantages of the iron-based amorphous alloy and its preparation method and application in degrading tetracycline antibiotics disclosed in the present invention are:
[0023] The iron-based amorphous alloy strip of the present invention has good amorphous forming ability, and the preparation process has more tolerant requirements on the reaction environment than the preparation process of metal organic framework materials, so it can be used on a large scale.
[0024] Moreover, as a metastable material, iron-based amorphous alloy has higher thermodynamic energy than the corresponding crystalline alloy and zero-valent iron powder. Therefore, the activation energy required for chemical reaction is lower than that of the corresponding crystalline alloy and zero-valent iron powder. It is easier to adsorb and react to degrade tetracycline antibiotics, thereby improving the removal rate of tetracycline antibiotics in water.
[0025] At the same time, the iron-based amorphous alloy of the present invention is less likely to be passivated on its surface during the degradation reaction, can maintain its activity for a longer period of time compared to iron powder, and is more easily recyclable after the degradation reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a comparison chart of the removal rate of tetracycline hydrochloride in Example 1 and Comparative Example 1;
[0027] Figure 2 The kinetic fitting diagram of removing tetracycline hydrochloride in Example 1 and Comparative Example 1;
[0028] Figure 3 This is a comparison chart of total organic carbon removal rates of Example 1 and Comparative Example 1 after reacting in tetracycline hydrochloride wastewater for 30 minutes;
[0029] Figure 4 This is a comparison chart of the removal rates of tetracycline hydrochloride at different initial pH values using an iron-based amorphous alloy in Examples 1-7;
[0030] Figure 5This is a comparison chart of the reaction rates of using an iron-based amorphous alloy to remove tetracycline hydrochloride at different initial pH values in Example 1-7;
[0031] Figure 6 This is a graph showing the removal rate of oxytetracycline hydrochloride by using an iron-based amorphous alloy in Example 8;
[0032] Figure 7 This is a kinetic fitting diagram of removing oxytetracycline hydrochloride using an iron-based amorphous alloy in Example 8;
[0033] Figure 8 This is a graph showing the removal rate of chlortetracycline hydrochloride by using an iron-based amorphous alloy in Example 9;
[0034] Fig. 9 This is the kinetic fitting diagram of removing chlortetracycline hydrochloride using iron-based amorphous alloy in Example 9. DETAILED DESCRIPTION
[0035] The iron-based amorphous alloy disclosed in the present invention has a molecular formula of FexSiyBz, wherein x, y, and z represent the atomic percentages of Fe, Si, and B in the alloy, respectively, 74≤x≤84, 6≤y≤16, 6≤z≤16, and x+y+z=100.
[0036] Furthermore, the present disclosure also provides a method for preparing the above-mentioned iron-based amorphous alloy, comprising the following steps:
[0037] S1, melting the raw materials in a melting furnace in an inert atmosphere according to proportion to prepare an iron-based amorphous alloy;
[0038] S2. The iron-based amorphous alloy prepared in step S1 is prepared into an iron-based amorphous alloy strip by a single-roller strip spinning method.
[0039] S3, cutting the iron-based amorphous alloy strip into sheet strips with a length of 10 mm.
[0040] Wherein, the thickness of the iron-based amorphous alloy strip is 10 μm to 200 μm.
[0041] Specifically, to prepare Fe 78 Si8B 14 Take this as an example to illustrate:
[0042] S1. Fe, Si and B are weighed according to their component contents, put into a smelting furnace, and smelted in an inert gas atmosphere to form an iron-based amorphous alloy; optionally, the inert atmosphere can be a helium atmosphere or an argon atmosphere.
[0043] S2, preparing the iron-based amorphous alloy obtained in step S1 into an iron-based amorphous alloy strip by a single-roller strip spinning method, the specific steps comprising:
[0044] S201, placing the alloy obtained in step S1 into a melting furnace, and induction heating it in an inert gas atmosphere until it is molten;
[0045] S202, pouring the molten alloy into the nozzle package, spraying the molten alloy onto the surface of the cooling roller through the nozzle, and cooling to form an iron-based amorphous alloy strip.
[0046] It should be noted that before single-roller belt spinning, the distance between the nozzle and the cooling roller needs to be adjusted to 1-2 mm, preferably, to 1.5 mm; and the speed of the cooling roller is set to 55 m / s, and then the single-roller belt spinning operation is performed.
[0047] After the single-roller strip-spinning operation is completed, the iron-based amorphous alloy strip obtained in step S2 is cut into sheet strips with a length of 10 mm.
[0048] During the alloy preparation process, smelting is required in an inert gas atmosphere to ensure that the metal material is not oxidized. By smelting in an inert gas atmosphere, oxygen can be effectively isolated and the metal material can be protected from oxidation and contamination.
[0049] During the single-roll strip-spinning operation, smelting is also required. In order to ensure that the alloy material is not oxidized and contaminated, smelting is also required to be carried out in an inert gas atmosphere.
[0050] Furthermore, the present disclosure also provides an application of an iron-based amorphous alloy, which is applied to the treatment of wastewater containing tetracycline antibiotics to degrade tetracycline antibiotics, including tetracycline hydrochloride, chlortetracycline hydrochloride and oxytetracycline hydrochloride. 78 Si8B 14 As an example, zero-valent iron powder is used as a comparative example, and the experimental content and conclusion are explained.
[0051] Example 1
[0052] Pour 250 ml of wastewater containing tetracycline hydrochloride into the reaction tank, wherein the concentration of tetracycline hydrochloride in the wastewater is 40 mg / L; put 2.5 g of the iron-based amorphous alloy strip prepared by the above preparation method into the reaction tank, and adjust the pH value to 5.0; place the reaction tank in a 35°C water bath, add a stirrer to the reaction tank, adjust the stirrer speed to 350 r / min, and carry out the reaction.
[0053] Example 2
[0054] Similar to Example 1, except that the pH value was adjusted to 3.0.
[0055] Example 3
[0056] Similar to Example 1, except that the pH value was adjusted to 4.0.
[0057] Example 4
[0058] Similar to Example 1, except that the pH value was adjusted to 6.0.
[0059] Example 5
[0060] Similar to Example 1, except that the pH value was adjusted to 7.0.
[0061] Example 6
[0062] Similar to Example 1, except that the pH value was adjusted to 9.0.
[0063] Example 7
[0064] Similar to Example 1, except that the pH value was adjusted to 11.0.
[0065] Example 8
[0066] Similar to Example 1, the difference is that 250 ml of wastewater containing oxytetracycline hydrochloride is poured into the reaction tank, and the concentration of tetracycline hydrochloride in the wastewater is 40 mg / L.
[0067] Example 9
[0068] Similar to Example 1, the difference is that 250 ml of wastewater containing chlortetracycline hydrochloride is poured into the reaction tank, and the concentration of tetracycline hydrochloride in the wastewater is 40 mg / L.
[0069] Comparative Example 1
[0070] Similar to Example 1, the difference is that 2.5 g of zero-valent iron powder with a particle size of 100 mesh is put into the reaction tank.
[0071] In the above embodiments and comparative examples, 5 mL of solution was extracted at regular intervals during the reaction, the sample was filtered through a 0.22 μm filter membrane, and the spectrum was measured by a UV-visible photometer. The time for taking the solution was 0 minute, 2 minute, 5 minute, 10 minute, 20 minute, and 30 minute, respectively.
[0072] Figure 1 to Figure 3 It is a comparison chart of Example 1 and Comparative Example 1, including removal rate comparison, kinetic fitting comparison and total organic carbon removal rate comparison. Figure 1 It can be seen that after 5 minutes of reaction, the removal efficiency of tetracycline hydrochloride using zero-valent iron powder and iron-based amorphous alloy was 30.3% and 64.2%, respectively, and at 30 minutes, the removal efficiency of the iron-based amorphous alloy was still higher than that of the zero-valent iron powder, indicating that the amorphous alloy with a metastable structure does have a more efficient removal efficiency than the crystalline zero-valent iron powder.
[0073] also, Figure 2 The kinetic fitting diagrams of removing tetracycline hydrochloride in Example 1 and Comparative Example 1 are shown. The reaction rate k is obtained by first-order reaction kinetic fitting. obs By comparison, it was found that the removal rate of tetracycline hydrochloride by iron-based amorphous alloy was 2.75 times that of zero-valent iron powder.
[0074] and, Figure 3 This is a comparison chart of the total organic carbon removal rates of Example 1 and Comparative Example 1 in tetracycline hydrochloride wastewater after reaction for 30 minutes. The organic carbon content in the solution can better reflect the final mineralization result of tetracycline hydrochloride. The figure shows that the total organic carbon removal rate in the solution after the iron-based amorphous alloy reacts for 30 minutes is 84.9%, which is much higher than 76% of zero-valent iron powder. This shows that the iron-based amorphous alloy can effectively remove tetracycline hydrochloride antibiotics and reduce the organic matter content in the solution.
[0075] Examples 1 to 7 are comparisons of the ability of iron-based amorphous alloys to degrade tetracycline hydrochloride in tetracycline hydrochloride wastewater under different pH conditions. Figure 4-5 As shown, Figure 4 This is a comparison chart of the removal rate of tetracycline hydrochloride using iron-based amorphous alloy at different initial pH values. Figure 5 This is a comparison chart of the reaction rates of removing tetracycline hydrochloride using iron-based amorphous alloy at different initial pH values.
[0076] Depend on Figure 4 It can be seen that when 4.0≤pH≤9.0, 99% of tetracycline hydrochloride can be removed from wastewater within 30 minutes; Figure 5 It can be seen that when the solution pH is in the range of 4.0 to 7.0, the reaction rate k obs Similarly, when the pH reaches 9.0, the reaction rate drops significantly. The inventors believe that the reasons are as follows:
[0077] Tetracycline hydrochloride has three pKa values (3.3, 7.7, 9.7). When pH < 3.3, tetracycline hydrochloride is mainly present in the solution as TCH3 + When pH is 3.3<7.7, tetracycline hydrochloride exists mainly in the form of TCH2 0 When pH is 7.7<9.7, tetracycline hydrochloride exists in the solution mainly in the form of TCH - When pH>9.7, tetracycline hydrochloride exists in the solution mainly in the form of TC2 -The corrosion products (FeO, Fe2O3, Fe3O4, FeOOH) produced by the iron-based amorphous alloy during the corrosion process are effective adsorbents. When the pH of the solution is less than 8.0, the iron oxide is positively charged and can adsorb anions and zwitterions on the surface of the iron-based amorphous alloy through electrostatic action; the iron-based amorphous alloy can produce hydrogen radicals (H·) with reduction activity, which react with the organic ions adsorbed on the surface of the iron-based amorphous alloy to undergo dehydrogenation reactions, double bond addition reactions and single electron transfer reactions. Therefore, the removal rate of tetracycline hydrochloride is high when the solution environment pH is between 4.0 and 9.0, while the removal rate of tetracycline hydrochloride is low when the pH is 3.0 or pH 11.0.
[0078] In summary, it can be determined that the most suitable pH range for degrading tetracycline hydrochloride is between 4.0 and 9.0. Since one of the pKa values of tetracycline hydrochloride is 3.3, the inventors believe that the most suitable pH range for degrading tetracycline hydrochloride is between 3.3 and 9.0.
[0079] Figure 6 This is a graph showing the removal rate of oxytetracycline hydrochloride by using an iron-based amorphous alloy in Example 8; Figure 7 Example 8 Kinetic fitting diagram of removing oxytetracycline hydrochloride using iron-based amorphous alloy; Figure 6 and Figure 7 It can be seen that when the reaction time is 20 min, the removal rate of oxytetracycline hydrochloride by using iron-based amorphous alloy is as high as more than 97%. In addition, the reaction rate k is obtained by first-order reaction kinetic fitting. obs Under this condition, the removal rate of oxytetracycline hydrochloride by iron-based amorphous alloy is as high as 0.257min -1 , far ahead of the currently commonly used biodegradation method.
[0080] Figure 8 This is a graph showing the removal rate of chlortetracycline hydrochloride by using an iron-based amorphous alloy in Example 9; Fig. 9 This is the kinetic fitting diagram of removing chlortetracycline hydrochloride using an iron-based amorphous alloy in Example 9; Figure 8 and Fig. 9 It can be seen that after 20 minutes of reaction, the removal rate of chlortetracycline hydrochloride using iron-based amorphous alloy is close to 97%. In addition, the reaction rate k is obtained by first-order reaction kinetic fitting. obs Under this condition, the removal rate of chlortetracycline hydrochloride by iron-based amorphous alloy is as high as 0.323min -1 , far ahead of the currently commonly used biodegradation method.
[0081] In the description of the present disclosure, it is necessary to understand that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, horizontal" and "top, bottom" are usually based on the directions or positional relationships shown in the drawings, and are only for the convenience of describing the present disclosure and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the device or element referred to must have a specific orientation or be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the scope of protection of the present disclosure.
[0082] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present disclosure.
Claims
1. An iron-based amorphous alloy, characterized in that: The molecular formula of the iron-based amorphous alloy is FexSiyBz, wherein x, y, and z represent the atomic percentages of Fe, Si, and B in the alloy respectively, 74≤x≤84, 6≤y≤16, 6≤z≤16, and x+y+z=100.
2. The method for preparing the iron-based amorphous alloy according to claim 1, characterized in that: The steps include: S1, melting the raw materials in a melting furnace in an inert atmosphere according to proportion to prepare an iron-based amorphous alloy; S2. The iron-based amorphous alloy prepared in step S1 is prepared into an iron-based amorphous alloy strip by a single-roller strip spinning method.
3. The preparation method according to claim 2, characterized in that: The thickness of the iron-based amorphous alloy strip is 10 μm to 200 μm.
4. The preparation method according to claim 2, characterized in that: Also includes: S3, cutting the iron-based amorphous alloy strip into sheet strips with a length of 10 mm.
5. The use of the iron-based amorphous alloy according to claim 1 or the iron-based amorphous alloy prepared by the preparation method according to any one of claims 2 to 4, characterized in that: The iron-based amorphous alloy is applied to the treatment of wastewater containing tetracycline antibiotics to degrade the tetracycline antibiotics.
6. The use according to claim 5, characterized in that: In the wastewater containing tetracycline antibiotics, the concentration of the tetracycline antibiotics is 10-200 mg / L.
7. The use according to claim 5, characterized in that: The pH value of the wastewater containing tetracycline antibiotics is 3.3-9.
8. The use according to claim 7, characterized in that: The pH value of the wastewater containing tetracycline antibiotics is 4-9.
9. The use according to claim 5, characterized in that: The added amount of the iron-based amorphous alloy strip is greater than or equal to 10 g / L.
10. The use according to claim 5, characterized in that: The temperature of the wastewater containing tetracycline antibiotics is 30-40°C.
Citation Information
Patent Citations
Printing and dyeing wastewater treatment method
CN105314726A
Oxytetracycline wastewater treatment method
CN107176724A
Method for regulating and controlling density of amorphous alloy
CN109702157A
Fe-Si-B amorphous alloy strip, preparation method thereof and application of Fe-Si-B amorphous alloy strip in degradation of azo dye wastewater
CN109811278A
Porous iron-based amorphous / copper double-alloy composite material and preparation method and application thereof
CN114807661A